Pengaruh Lingkungan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Putra Langgeng Perkasa Di Tangerang Selatan - Tasya Gunawan; Prasetyo Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of Environment and Work Discipline on Employee Performance at PT Putra Langgeng Perkasa, South Tangerang, both partially and simultaneously. The research employed a quantitative method. The sampling technique used was saturated sampling, resulting in a total sample of 112 respondents.Data analysis techniques included validity testing, reliability testing, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of the study indicate that the work environment has a positive and significant effect on employee performance, with the regression equation Y = 43.454 + 0.126X₁. The correlation coefficient obtained was 0.409, indicating a moderate relationship between the two variables. The coefficient of determination was 4.5%. Hypothesis testing showed that t₍count₎ > t₍table₎ (2.495 > 1.982); therefore, H₀ was rejected and H₁ was accepted, indicating a significant effect of the work environment on employee performance. Furthermore, work discipline has a positive and significant effect on employee performance, with the regression equation Y = 39.375 + 0.212X₂. The correlation coefficient was 0.874, indicating a very strong relationship between the variables. The coefficient of determination was 72.9%. Hypothesis testing results showed t₍count₎ > t₍table₎ (17.325 > 1.982); thus, H₀ was rejected and H₂ was accepted, indicating a significant effect of work discipline on employee performance. Simultaneously, work environment and work discipline have a positive and significant effect on employee performance, as indicated by the regression equation Y = 35.288 + 0.115X₁ + 0.211X₂. The correlation coefficient obtained was 0.881, indicating a very strong relationship between the variables. The coefficient of determination was 77.3%. Hypothesis testing showed F₍count₎ > F₍table₎ (141.256 > 3.130); therefore, H₀ was rejected and H₃ was accepted, indicating that environment and work discipline simultaneously have a significant effect on employee performance.